Dynamics of changes in S-100 protein and neuron-specific enolase in rabbits with ocular contusion and its correction with L-lysin– (S)-2,6-diaminohexanoic acid 3-methyl-1,2,4-triazolyl-5-thioacetate - Shelest, O. E.; Semenenko, S. I.; Saienko, А. V.; Vozniuk, L. A.; Semenenko, O. М.; Nefodova, O. О.; Morozova, O. V.; Шелест, О. Є.; Семененко, С. І.; Саєнко, А. В.; Вознюк, Л. А.; Семененко, О. М.; et al. (My University, 2025)
Eye injuries are a serious medical and social problem, the relevance of which is significantly increasing in conditions of military conflicts. Damage to the visual organs can cause temporary or permanent vision loss, significantly affecting the quality of life of those affected and their ability to work. In peacetime, the main causes are domestic, industrial, and sporting incidents. At the same time, in military conditions, up to 16 % of all combat injuries occur to the organs of vision, of which about 80 % are associated with the effects of blast waves. Biochemical markers are an important aspect of understanding the mechanisms of such damage. In particular, the enzyme neuron-specific enolase and the S100 protein are indicators of nerve tissue damage. neuronspecific enolase, an intracellular enzyme, indicates damage to neuronal membranes, while increased levels of S100 protein indicate an inflammatory reaction in glial tissue, active division of neuroglial cells, and neuroapoptosis. The presence of these markers in the blood allows us to assess the severity of damage and the effectiveness of therapeutic measures. The relevance of neuroprotection in the treatment of eye injuries is due to the need to protect and restore the nervous structures of the eye, particularly the retina and optic nerve. The study found that therapy with Angiolin eye drops significantly reduced the markers of neurodestruction in the serum of rabbits with ocular contusion. Namely, neuron-specific enolase decreased by 87.2 % and S100 by 89.9 %. The results of the study confirm the pronounced neuroretinoprotective effect of the drug Angiolin. Очні травми є серйозною медичною та соціальною проблемою, актуальність особливо зростає в умовах військових конфліктів. Ушкодження зорових органів можуть спричиняти тимчасову або стійку втрату зору, що суттєво впливає на якість життя постраждалих та їхню працездатність. У мирний час основними причинами є побутові, виробничі та спортивні інциденти, тоді як у військових умовах до 16 % всіх бойових ушкоджень припадає на органи зору, з яких близько 80 % пов'язані з дією вибухових хвиль. Важливим аспектом у розумінні механізмів таких ушкоджень є біохімічні маркери. Зокрема, фермент нейрон-специфічна енолаза (NSE) та білок S100 є показниками ушкодження нервової тканини. NSE, що є внутрішньоклітинним ферментом, свідчить про пошкодження мембран нейронів, тоді як підвищення рівня білка S100 вказує на запальну реакцію в гліальній тканині, активний поділ клітин нейроглії та нейроапоптоз. Наявність цих маркерів у крові дозволяє оцінити тяжкість ушкоджень та ефективність терапевтичних заходів. Актуальність нейропротекції в лікуванні очних травм обумовлена необхідністю захисту та відновлення нервових структур ока, зокрема сітківки та зорового нерва. Проведене дослідження виявило, що терапія очними краплями Ангіолін сприяла значному зниженню рівнів маркерів нейродеструкції в сироватці крові кроликів з контузійною травмою ока, а саме: NSE зменшився на 87,2 %, а S100 – на 89,9 %. Результати підтверджують виражену нейроретинопротективну дію препарату Ангіолін.
Динаміка змін білку S-100 та нейрон-специфічної енолази у кролів при контузійній травмі ока та її корекція l-лізином – (S)-2,6-діаміногексанової кислоти 3-метил-1,2,4-тріазоліл-5-тіоацетатом
Keywords: ocular contusion; optic nerve; retina; neuron-specific enolase; S100 protein; neuroprotection; контузійна травма ока; зоровий нерв; сітківка; нейрон-специфічна енолаза; білок S100; нейропротекція